키네틱 타이포그래피 원리에 기반을 둔 다이나믹 포스터 디자인의 한자 표현방식에 관한 연구 - ‘24절기’ 테마 포스터를 중심으로 - 저자읍(Ziyi Chu); 박용진(Yong-Jin Park) (한국콘텐츠학회논문지, 2022)
Based on the kinetic typography principle and the structure features of Chinese characters, this study took the Chinese'24 solar terms' theme dynamic poster as the research object, explored the visual expression of dynamic Chinese characters, and tried to summarize the visual expression law of Chinese characters in dynamic poster design. It can be found that, there could be 6 different types of Chinese character expressions in the 24 solar terms poster design. Among them, 'Drawing' design method has the meaning of text structure and form expression, and 'Assembling' design method has the meaning of text stroke and texture association, also, 'Forming' design method bring its meaning through stroke deformation, 'Transforming' design method conveys the content through text disintegration, 'Replacing' design method mainly bring the meaning through simulation, while 'Rotation' design method always express through visual three-dimensional and space. Finally, the findings could not only provide analytical logic and methods for the expression of Chinese characters in dynamic poster design, but also fill the lack of formative research on dynamic Chinese characters, which hopefully provide basic information for the research related to dynamic Chinese character structure, as well as the dynamic poster designers. 본 연구는 키네틱 타이포그래피의 원리와 한자의 특징을 근거로 중국의 '24절기'주제의 다이나믹 포스터를 연구 대상으로 선정하고 정성 방법을 통해 한자 키네틱 타이포그래피의 표현 유형을 분석한다. 다이나믹 포스터 디자인 중 한자의 시각 표현 법칙을 정리한다. 24절기 다이나믹 포스터가 디자인한 한자 표현은 6가지 유형으로 나눠 각기 다른 것으로 나타났다. 그중에 그리기 유형의 시각적 표현 규칙은 문자의 구조 형태 표현, 결합 유형의 시각적 표현 규칙은 문자의 필획과 텍스처 형태간의 연관성, 형성 유형의 시각적 표현 규칙은 필획의 변형, 변환 유형의 디자인 기법은 문자의 해체, 치환 유형의 시각적 표현 규칙은 시뮬레이션을, 회전 유형의 시각적 표현 규칙은 시각적 입체감과 공간감을 제시한 부분의 의의가 있어 보이다. 본 연구는 다이나믹 포스터에 나타난 한자 표현에 기초적인 자료와 분석논리를 제공하여 한자 키네틱 타이포그래피관련 연구가 부족한 점을 보완 하며 한자 키네틱 타이포그래피 구조 및 다이나믹 포스터 디자인 관련 분야에 참고가 될 것으로 기대된다.